Characterization and chemoproteomic profiling of protein O-GlcNAcylation in SOD1-G93A mouse model - Yi Hao; Zhongzhong Li; Xinyan Du; Qingsong Xie; Dongxiao Li; Shaoyuan Lei; Yansu Guo (Molecular Medicine, 2025)
Abstract Background Amyotrophic lateral sclerosis (ALS) is a devastating motor neuron disease. Protein O-linked β-N-acetylglucosamine (O-GlcNAc) modification has been found to affect the processing of several important proteins implicated in ALS. However, the overall level and cellular localization of O-GlcNAc during ALS progression are incompletely understood, and large-scale profiling of O-GlcNAcylation sites in this context remains unexplored. Methods By using immunostaining analysis and chemoenzymatic labeling-based quantitative chemoproteomics, we assayed O-GlcNAcylation dynamics of lumbar spinal cords from SOD-G93A mice and their non-transgenic (NTG) littermates, the most widely used animal model for studying ALS pathogenesis. Results We discovered that the global O-GlcNAcylation was significantly reduced at the disease end stage. Correlatively, a great increase of OGA was observed. Immunohistochemistry and immunofluorescence analysis showed a higher proportion of O-GlcNAc-positive neurons in the NTG group, while O-GlcNAc colocalization with astrocytes/microglia was elevated in SOD1-G93A mice. Moreover, we reported the identification of 568 high-confidence O-GlcNAc sites from end-stage SOD1-G93A and NTG mice. Of the 568 sites, 226—many of which occurred on neuronal function and structure-related proteins—were found to be dynamically regulated. Conclusion These data provide a valuable resource for dissecting the functional role of O-GlcNAcylation in ALS and shed light on promising therapeutic avenues for ALS. The chemoenzymatic labeling-based chemoproteomic approach is applicable for probing O-GlcNAc dynamics in various pathological processes.